Caracterización de la comunidad vegetal en una lechería comercial en la provincia de Matanzas, Cuba - Flavia García-Sánchez; Tania Sánchez-Santana; Luis Lamela-López; Dariel Morales-Querol; Fernando Ruz-Suarez (Pastos y Forrajes, 2022)
Objective: To characterize the plant community of the pastureland in a dairy farm under commercial conditions in Matanzas province, Cuba.